2012
DOI: 10.1111/ppe.12010
|View full text |Cite
|
Sign up to set email alerts
|

Preterm Birth and Birthweight‐for‐Gestational Age among Immigrant Women in Denmark 1978–2007: A Nationwide Registry Study

Abstract: Immigration was more strongly related to SGA than to preterm delivery. Observed differences in birth outcomes varied by age at immigration and length of residency in Denmark.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 34 publications
(30 reference statements)
2
26
1
2
Order By: Relevance
“…Thus, there might have been less pressure towards selection to migration to Norway in comparison to other receiving countries. As to recent immigrants, we did not confirm an elevated PTD risk, as reported from Denmark [11]. …”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…Thus, there might have been less pressure towards selection to migration to Norway in comparison to other receiving countries. As to recent immigrants, we did not confirm an elevated PTD risk, as reported from Denmark [11]. …”
Section: Discussioncontrasting
confidence: 81%
“…A study from Canada found that the risk of PTD increased with longer length of residence and exceeded the risk among non-immigrants after 10 years of residence [25]. One Danish study found a U-shaped association between PTD and the length of residence [11]. Few studies of migrants to Europe have included length of residence in the study of PTD, and none of these studies have differentiated between PTD subtypes.Facing a steep increase in births to immigrant women in Europe, this study aimed to determine if the risk of spontaneous and non-spontaneous preterm delivery in Norway vary according to the length of residence and the country of birth.…”
Section: Introductionmentioning
confidence: 99%
“…Turkish-born women and Pakistani-born women had an increased risk of very preterm delivery as well as moderate preterm delivery compared with Danish-born women but among Lebaneseborn a lower risk for very preterm delivery and among Somali-born women a lower risk for moderate preterm delivery were also observed. No difference was found for women from former Yugoslavia compared with Danishborn women [8]. In regards to small-for-gestational age (SGA) delivery, an increased risk was seen among all immigrant groups compared with Danish-born women [8].…”
Section: Pregnant Women and Infantsmentioning
confidence: 74%
“…No difference was found for women from former Yugoslavia compared with Danishborn women [8]. In regards to small-for-gestational age (SGA) delivery, an increased risk was seen among all immigrant groups compared with Danish-born women [8].…”
Section: Pregnant Women and Infantsmentioning
confidence: 74%
“…Higher prevalence of low birth weight infants was found among Pakistani immigrants in the Europe (Pedersen, Mortensen, Gerster, Rich-Edwards, & Andersen, 2012;Seaton, Yadav, Field, Khunti, & Manktelow, 2011). Pakistani pregnant women in Norway also had higher prevalence rate of gestational diabetes (9/1000) compared to Norwegian women (3.6/1000) (Vangen et al, 2003).…”
Section: Maternal and Child Outcomes Among Pakistani Immigrantsmentioning
confidence: 88%